Marine Debris Floating in Arctic and Temperate Northeast Atlantic Waters - Tekman, Mine B.; Gutow, Lars; Bergmann, Melanie (Frontiers in Marine Science, 2022)
Floating marine debris is ubiquitous in marine environments but knowledge about quantities in remote regions is still limited. Here, we present the results of an extensive survey of floating marine debris by experts, trained scientists from fields other than pollution or non-professional citizen scientists. A total of 276 visual ship-based surveys were conducted between 2015 and 2020 in the Northeast (NE) Atlantic from waters off the Iberian Peninsula to the Central Arctic, however, with a focus on Arctic waters. Spatiotemporal variations among regional seas (Central Arctic, Barents Sea, Greenland Sea, Norwegian Sea, North Sea) and oceanic regions (Arctic waters and the temperate NE Atlantic) were explored. The overall median debris concentration was 11 items km-2, with considerable variability. The median concentration was highest in the North Sea with 19 items km-2. The Nordic seas, except the Central Arctic showed median concentrations ranging from 9 to 13 items km-2. Plastic accounted for 91% of all floating items. Miscellaneous fragments, films, ropes and nets, packaging materials, expanded polystyrene and straps were the most frequently observed plastic types. Although the median debris concentration in the Central Arctic was zero, this region was not entirely free of floating debris. The variations between regional seas and oceanic regions were statistically not significant indicating a continuous supply by a northward transportation of floating debris. The data show a slight annual decrease and clear seasonal differences in debris concentrations with higher levels observed during summer. A correlation between debris concentrations and environmental and spatial variables was found, explaining partly the variability in the observations. Pollution levels were 500 times lower than those recorded on the seafloor indicating the seafloor as a sink for marine debris. The Arctic was characterised by similar pollution levels as regions in temperate latitudes highlighting that Arctic ecosystems face threats from plastic pollution, which add to the effects of rapid climate change.